TYPES OF INFECTIONS: PATHOPHYSIOLOGY AND CLINICAL IMPLICATIONS - Razhabova Zebiniso Safarovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Infections are caused by various pathogens, including bacteria, viruses, fungi, and parasites, leading to diverse clinical manifestations. Understanding the different types of infections, their pathophysiological mechanisms, and their impact on human health is essential for effective diagnosis and treatment. This article explores the classification of infections, their modes of transmission, and management strategies.